Beyond State-Centric Security: Rethinking Human Insecurity in Africa through a People-Centred Lens - Onor, Kester C. (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2025)
Human (in)security in Africa is a multidimensional challenge influenced by political, economic, social, and environmental factors. Despite various security interventions, the continent continues to face armed conflicts, terrorism, weak governance, poverty, climate change, and forced displacement. This study examines the root causes and consequences of human insecurity in Africa and evaluates the effectiveness of shifting from state-centric to people-centred security approaches. Using a qualitative research design, the study applies human security theory and analyses case studies from the Sahel, Horn of Africa, and Great Lakes region. Data were obtained from documentary sources, reports, and scholarly literature to identify insecurity and governance deficits. Findings reveal that state-centric security frameworks have largely failed to address the lived realities of affected populations. Persistent vulnerabilities manifest in mass displacement, food insecurity, economic underdevelopment, and social fragmentation, further fueling cycles of violence and instability. The study advocates a people-centred security paradigm prioritising inclusive governance, economic resilience, and regional cooperation. It contributes to ongoing debates on African security governance and calls for policies emphasising human dignity and well-being over militarised responses to achieve sustainable peace and development.